Manufacturing of coir fibre-reinforced polymer composites by hot compression technique - Hasan, Mahbub; Hoque, Muhammad Enamul; Mir, Samia Sultana; Saba, Naheed; Salit, Mohd Sapuan (Springer International Publishing Switzerland, 2015)
This present chapter describes the manufacturing technique and properties of coir fibre-reinforced polypropylene composites manufactured using a hot press machine. The effects of basic chromium sulphate and sodium bicarbonate treatment on the physical and mechanical properties were also evaluated. Chemical treatment and fibre loading generally improved the mechanical properties. Five-hour basic chromium sulphate and sodium bicarbonate-treated coir-polypropylene had the best set of properties among all manufactured composites. Chemical treatment also improved water absorption characteristics. This proves that chemical treatment reduced the hydrophilicity of the coir fibre. Overall the hot compression technique was proved to be successful in manufacturing good quality coir reinforced polypropylene composites.